Factors affecting the purchase intention of non-certified halal Korean instant noodles - Rahmawati, Alissa Aulina; Aji, Hendy Mustiko (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose – This study aims to determine what factors encourage Muslim consumers to purchase non-halal MUI-certified instant noodles. Methodology – The sample for this study is selected using a purposive sampling technique with the criteria of Muslim respondents who never purchased non-halal MUI-certified instant noodles. This study collected 114 usable responses for further analysis. All data were analyzed using the PLS-SEM method. Finding – The results indicated that product knowledge has an effect on halal product awareness and intention to purchase non-halal MUI-certified Korean instant noodles. Intrinsic religiosity value does not affect halal product awareness, but halal product awareness significantly affects the intention to purchase non-halal MUI-certified Korean instant noodles. Finally, halal product knowledge positively links the purchase intention of non-halal MUI-certified Korean instant noodles. Implications – The results of this study are expected to help supermarkets, distributors, and the government to improve the supervision of products, especially Korean instant noodle products that do not yet have an MUI halal certificate.Originality – Studies that investigated intrinsic religiosity, halal product awareness, and knowledge toward purchase intention have been previously performed. However, the results are inconclusive. Besides, such studies in non-halal-certified Korean noodles are scarce. This study contributes to the literature by re-investigating these relationship in the context of non-halal-certified Korean noodles in Indonesia.